Physicochemical Properties of Halal Alternative Gelatin from Parrotfish (Scarus quoyi) Scales Optimized by Response Surface Methodology - Yulian, Muammar; Reza, Muhammad; Ramadani, Nofa; Hamama, Rosi; Fadhilah, Raudhatul; Akmal, Yusrizal; Abass, Kasim Sakran; Paujiah, Epa; Hajisamae, Sukree; Zulfahmi, Ilham (UIN Sunan Gunung Djati Bandung, 2025)
The increasing demand for halal-friendly gelatin, combined with concerns over health risks associated with mammalian sources, has created a need for alternative raw materials. Fish scales from local species, such as parrotfish, offer a sustainable and promising option that has yet to be extensively explored. The study aims to investigate the physicochemical properties of gelatin extracted from the scales of the parrotfish (Scarus quoyi) scales. Response Surface Methodology (RSM) was employed to determine the optimal concentration of hydrochloric acid (HCl) and immersion time to maximize yield and quality. Physicochemical properties, including yield, moisture content, ash content, pH, and viscosity, were evaluated, and the structural characteristics of the gelatin were analyzed using Fourier-Transform Infrared Spectroscopy (FTIR). All processing steps were conducted in compliance with Halal Critical Control Points (HCCPs) to ensure the final product remained free from cross-contamination with non-halal substances. Response surface methodology optimization identified 4% HCl concentration and 29.4 hours of immersion as optimal conditions. These conditions produce gelatin with a yield, moisture, ash, pH, and viscosity are 14.5%, 4%, 0.48%, 4.15, and 1.78 cP, respectively. FTIR analysis confirmed that the extracted gelatin exhibited absorption peaks consistent with those of commercial gelatin, indicating a functional group similarity. Compared to gelatin from other fish species, parrotfish gelatin demonstrated a competitive yield and notably low moisture content, thereby enhancing its stability and storage potential. These findings highlight the potential of parrotfish scales as a sustainable source of halal gelatin, contributing to waste reduction and offering a viable alternative to mammalian gelatin.